Ubuntu and the body: A perspective from theological anthropology as embodied sensing - Meiring, Jacob J. S. (Verbum et ecclesia, 2015)
The author asks whether the notion of ubuntu truly exists within contemporary South African society and how the experiencing of South Africans' embodiment can be connected to ubuntu - especially amongst black people. The notion of ubuntu is briefly explored within law and theology. The author has recently proposed a model for a contemporary theological anthropology as embodied sensing' which functions within the intimate relationship of the lived body, experiencing in a concrete life-world, language, and the more than'. It is from this perspective that the notion of ubuntu is explored.